Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/jp972787u
|View full text |Cite
|
Sign up to set email alerts
|

Exothermodynamic Relationships in Liquid Chromatography

Abstract: Exothermodynamic relationships in reversed-phase and hydrophobic interaction chromatography, with the temperature, organic modifier or salt concentration, and carbon number of the eluite and of the stationary phase ligate as the operating variables, are classified and the links between various linear free energy relationships established. Starting from Martin's relationship based on group additivity, we arrive at two linear free energy relationships:  one between the logarithmic retention factors, κ, obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 107 publications
(196 reference statements)
1
50
0
Order By: Relevance
“…Reversely, an obvious different EEC can certify different retention or enantioseparation mechanisms [23]. Applying Martin's additive-freeenergy relationship [13], a functional group contribution to thermodynamic quantities can be written as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reversely, an obvious different EEC can certify different retention or enantioseparation mechanisms [23]. Applying Martin's additive-freeenergy relationship [13], a functional group contribution to thermodynamic quantities can be written as…”
Section: Discussionmentioning
confidence: 99%
“…Many extrathermodynamic relationships have been developed to facilitate the understanding of chromatographic retention and separation mechanism [13]. Typically, it has been demonstrated that the extrathermodynamic relationship derived from homologous series of analytes with additive group such as methylene or phenyl is able to provide useful information on chromatographic behavior [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Thermodynamic effects in RPLC have been the subject of previous research [38][39][40][41]. Significant changes in shape selectivity are observed with changes in temperature (Certificate of Analysis, https://srmors.nist.gov/view_de-tail.cfm?srm=869A), and an insight into the temperature dependence of alkyl chain conformations has been provided by Fourier transform infrared spectroscopy studies of chromatographic sorbents [42].…”
Section: Introductionmentioning
confidence: 99%
“…Regularising the structures via MO-PAC version 6, as implemented in SYBYL, using AM1, gave rise to the same CoMFA results. MR.lff 1 compounds, though congeneric depicted (some similar moieties present in molecules) as to the need of QSAR and QSRR studies [19,20]. On the other hand, QSRR studies demonstrate that a single physicochemical descriptor is not easily found for such complex retention mechanisms, mainly when they involve chiral recognition problems.…”
Section: Introductionmentioning
confidence: 99%